Interface Pressure of Lycra Orthosis at Different Postures in Children with Cerebral Palsy (CP) - Shaari, Ida Hasni; Abu Osman, Noor Azuan; Shasmin, Hanie Nadia (Penerbit Universiti Kebangsaan Malaysia, 2018)
Medical compression garment functions by exerted interface pressure between the fabric and skin. Yet, none of the previous studies have determine the pressure level of Lycra based orthosis. The current work aimed to determine the pressure level of Lycra orthosis at different postures in children with CP. Five (5) children with CP were recruited. Each were given a custom made Lycra orthosis. Two Tekscan medical sensor were placed over lateral side of upper garment and pants. The pressure was recorded when the child was in sitting, sit-to-stand (STS) and standing postures. There are significant differences of the interface pressure between each children, at different postures. The highest pressure recorded over upper garment is 122 mmHg and 120 mmHg over pants, both during sitting position. Overall, the Lycra orthosis exerted highest pressure over top garments than pants during sitting position.